Effect of Hydrogenation Process in Several Palm Oil Derivatives on Its Application as Edible Wax to Replace Paraffin in Wax Applications - Ahmad Husni Lubis; Puspasari, Ifa; Diana (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Wax is mostly produced using paraffin as its formulation, but nowadays, for food safety and environmental reasons, edible wax has become highly possible as a substitute. The hydrogenation process has been carried out on several derivatives of palm oil, namely refined palm stearine (RPS), refined palm oil (RPO), palm soft stearin (SST), Palm mid-olein (MOL), and Palm Mid Fraction (PMF) through 3 types of hydrogenation processes, namely: (1) complete hydrogenation with a target iodine value <1, (2) partial hydrogenation with limiting hydrogen gas consumption, and (3) partial hydrogenation with limiting reaction time. The hydrogenated products were characterized and compared to commercial paraffin and wax according to several parameters such as Solid Fat Content, crystallization rate, melting rate, melting point, smoke point, and flash point. Furthermore, we applied the hydrogenated products to both the wax products and a mixture of hydrogenated and paraffin products. The wax produced was then evaluated based on several parameters, such as hardness, combustion flame, melting diameter, and combustion time. The findings concluded that all hydrogenated products can be used as raw materials for wax, either their self or hydrogenated and paraffin formulation products. Waxes made from Refined Hydrogenated Palm Stearin (RHPS)-1 and Refined Hydrogenated Palm Oil (RHPO)-1 are the hardest wax in terms of texture. In contrast, in the case of flame, the waxes made from hydrogenated products formulated with paraffin and paraffin itself have brighter flame than the others and Refined Hydrogenated Soft Stearin (RHSST)-1 and Refined Hydrogenated Palm Mid Fraction (RHPMF)-1 waxes are the waxes that burn the longest. Each wax has certain characteristics that can be related to the hydrogenated product used. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action